Muskar (Myra / Lykia) iki yazıta addendum et corrigendum - (:unkn) unknown (My University, 2011)
0

In this article, two sarcophagi inscriptions are reexamined from the eastern necropolis of an ancient settlement whose name has not been documented certainly yet but is supposed to be the ancient city of Tragalassos located in the Asartepe site of the Muskar (Belören) village of Demre district in Antalya province. Although these two inscriptions were published before in Petersen – von Luschan 1889: 41, no. 75–76, as a result of our researches, we made some addenda and corrigenda for the inscriptions.
Muskar (Myra/Lycia): Addendum and corrigendum for two inscriptions
Keywords: Arkeoloji